2020
DOI: 10.5194/essd-12-563-2020
|View full text |Cite
|
Sign up to set email alerts
|

A global gridded (0.1° × 0.1°) inventory of methane emissions from oil, gas, and coal exploitation based on national reports to the United Nations Framework Convention on Climate Change

Abstract: Abstract. Individual countries report national emissions of methane, a potent greenhouse gas, in accordance with the United Nations Framework Convention on Climate Change (UNFCCC). We present a global inventory of methane emissions from oil, gas, and coal exploitation that spatially allocates the national emissions reported to the UNFCCC (Scarpelli et al., 2019). Our inventory is at 0.1∘×0.1∘ resolution and resolves the subsectors of oil and gas exploitation, from upstream to downstream, and the different emis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
136
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(144 citation statements)
references
References 25 publications
2
136
0
Order By: Relevance
“…We supersede it for the US with the gridded version of the Environmental Protection Agency inventory for 2012 (Maasakkers et al, 2016). We further supersede it globally for fuel (oil, gas, and coal) exploitation with the inventory of Scarpelli et al (2020) for 2012, which disaggregates spatially the national emissions reported to the United Nations Framework Convention on Climate Change (UNFCCC) (di.unfccc.int). All anthropogenic emissions are assumed to be aseasonal, except manure management for which we apply local temperature-dependent corrections (Maasakkers et al, 2016), and rice cultivation for which we apply gridded seasonal scaling factors from B.…”
Section: Prior Estimatesmentioning
confidence: 99%
See 2 more Smart Citations
“…We supersede it for the US with the gridded version of the Environmental Protection Agency inventory for 2012 (Maasakkers et al, 2016). We further supersede it globally for fuel (oil, gas, and coal) exploitation with the inventory of Scarpelli et al (2020) for 2012, which disaggregates spatially the national emissions reported to the United Nations Framework Convention on Climate Change (UNFCCC) (di.unfccc.int). All anthropogenic emissions are assumed to be aseasonal, except manure management for which we apply local temperature-dependent corrections (Maasakkers et al, 2016), and rice cultivation for which we apply gridded seasonal scaling factors from B.…”
Section: Prior Estimatesmentioning
confidence: 99%
“…This finding is consistent with Maasakkers et al 2019 the UNFCCC, and our posterior estimate of total anthropogenic emissions is closer to the country's latest submission to UNFCCC for 2010-2018 (16 Tg a -1 ; Figure 6). The new submission revises oil/gas methane emissions downward by a factor of 3 relative to the previous submission used as prior estimate in our inversion (Scarpelli et al, 2020).…”
Section: Anthropogenic Emissionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Natural sources include the ensemble mean of the WetCHARTS inventory version 1.2.1 (Bloom et al, 2017) for wetlands, open fires from the Global Fire Emissions Database version 4s with seasonal and interannual variability (van der Werf et al, 2017), termites from Fung et al (1991), and seeps from Etiope et al (2019) with global scaling to 2 Tg a -1 from Hmiel et al (2020). The default anthropogenic emissions are from EDGAR v4.3.2 (Janssens-Maenhout et al, 2019), and are superseded for fugitive fuel emissions (oil, gas, coal) by the Scarpelli et al (2020) inventory which spatially allocates national emissions reported by countries to the United Nations Framework Convention of Climate Change (UNFCCC). US anthropogenic emissions are further superseded by the gridded version of Inventory of U.S. Greenhouse Gas Emissions and Sinks from the Environmental Protection Agency (EPA GHGI) (Maasakkers et al, 2016).…”
Section: Prior Estimatesmentioning
confidence: 99%
“…Scarpelli et al (2020) published the newest gridded emission inventory available for comparison within in this study. It only contains CH 4 emissions from oil, natural gas and coal exploitation.…”
mentioning
confidence: 99%